Deixis Analysis of “The Last Letter From Your Lover (2021)” Movie Script By Jojo Moyes: English - Ade Irmanistanti; Lailatul Musyarofah; Yuliyanto Sabat (Journal of English Development, 2024)
The aim of this study was to analyze the types of deixis presented in the movie script of The Last Letter from Your Lover. The research utilized a descriptive qualitative method for data collection, employing documentary techniques. The study was based on Stephen Levinson's theory, which identifies 5 deixis types: person deixis, temporal deixis, spatial deixis, discourse deixis, and social deixis, as evidenced in the film script of The Last Letter From Your Lover (2021). The research data was extracted from the movie's dialogue, which has a duration of one hour and fifty minutes. The study seeks to categorize the 5 types of deixis and determine their frequencies in the film. The total of 1,409 deixes were identified in the movie script, with the following frequencies for each deixis type: person deixis (1,053), discourse deixis (98), temporal deixis (103), spatial deixis (95), and social deixis (60). Notably, person deixis was found to be the most common type of deixis in the study, with the highest frequency among all other type.